2020
DOI: 10.1038/s41598-020-71126-3
|View full text |Cite
|
Sign up to set email alerts
|

Architectural changes in alveolar bone for dental decompensation before surgery in Class III patients with differing facial divergence: a CBCT study

Abstract: this study aimed to investigate alveolar bone change around mandibular anterior teeth during orthodontic decompensation in patients with skeletal Class III malocclusion and different vertical facial patterns. The records of 29 consecutive Class III patients selected from those pending two-jaw orthognathic surgery were divided into low (≤ 28°), average (30°-37°), and high (≥ 39°) mandibular plane angle (MPA) groups. The DICOM files of CBCT scans and STL files of digital dental models, taken before (T1) and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The results of Yao’s study [ 26 ] are partially in consent with previous studies by Sun et al [ 27 ] and Lee et al [ 28 ], where bone margin of labial and lingual bone was also lowered after presurgical orthodontic treatment in class III patients; however, the total apical bone thickness did not change.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The results of Yao’s study [ 26 ] are partially in consent with previous studies by Sun et al [ 27 ] and Lee et al [ 28 ], where bone margin of labial and lingual bone was also lowered after presurgical orthodontic treatment in class III patients; however, the total apical bone thickness did not change.…”
Section: Resultssupporting
confidence: 80%
“…What is more interesting, the thickness of the alveolar bone was reduced after proclination (total bone thickness) [ 23 ] and retraction (lingual and buccal) of lower anterior teeth [ 35 , 36 ]. The results were similar for adults patients [ 26 , 28 , 31 , 32 , 33 , 34 ]. The only “gain” in the measured variable was for buccal thickness of mandibular incisor in bimaxillary protrusion patients treated with extraction therapy [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, in the past, the locations of the incisors were usually detected by measuring the thickness of the alveolar bone at the root apex without distinguishing between cortical and cancellous bone [ 13 ]. In this study, we improved the measurement methods of Mao and other researchers [ 14 , 15 ]: we evaluated the alveolar-bone morphology at the mandibular central incisors by measuring the thicknesses and areas of the cancellous and cortical bone at the level of the CEJ; 3, 6, and 9 mm below the CEJ; midway between the CEJ and the root apex; and at the root apex.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the measurements of alveolar bone height generally decreased after treatment (1), and alveolar bone height and thickness, especially at the cervical level,…”
Section: Introductionmentioning
confidence: 99%